The Implications of Presidential Instruction Number 1 of 2025 on Educational Budget Efficiency from a Siyāsah Māliyyah Perspective - Vega, Nadia Ratu Pratiwi; Relit Nur Edi; Ahmad Burhanuddin (Al-Risalah, 2026)
Presidential Instruction of the Republic of Indonesia Number 1 of 2025 concerning efficiency in the implementation of the State and Regional Budgets has direct implications for education budget management at the regional level. This study aims to analyze the implications of budget efficiency policies on education budget management at the Education and Culture Office of Lampung Province and to examine them from the perspective of Fiqh Siyasah. This research employs a qualitative method using normative and empirical approaches, with data collected through documentation studies, observation, and interviews with relevant stakeholders. The findings indicate that the implementation of budget efficiency policies in Lampung Province encourages sharper prioritization of education spending, particularly in improving learning quality, strengthening educational facilities, and ensuring equitable access to education. However, it also limits the flexibility of certain development programs considered less urgent. From the perspective of Fiqh Siyasah, budget efficiency policies are consistent with the principles of public welfare (maslahah), distributive justice, and the prohibition of waste (israf), provided that they do not undermine the fulfillment of citizens’ fundamental right to education. This study concludes that education budget efficiency can be aligned with the principles of Fiqh Siyasah when it is oriented toward sustainable educational services and overall public welfare.